A unified global costing framework catalyzes strategic investment in rice breeding - Katiyar, Sanjay K.; Pazhamala, Lekha T.; Das, Reshmi Rani; Musundire, Lennin; Bilaro, Atugonza; Kessy, Theodore T.; Asante, Maxwell Darko; Yadaw, Ram Baran; Chandel, Girish; Sao, Abhinav; Poudel, Amrit Prasad; Ofosu, Kirpal Agyemang (Frontiers in Plant Science, 2026)
Accelerating research investment and breeding innovation is critical to strengthening food system resilience and tackling the escalating food crisis across the Global South. To deliver transformative impact, rice breeding programs must transition into modern, focused, and data-driven systems that drive both financial and operational efficiency. Until recently, systematic cost assessment of rice breeding pipelines, crucial for strategic resource allocation, faster genetic gains, and enhanced varietal development, has been largely overlooked. To bridge this gap, we developed the Unified Global Costing Framework for Rice Breeding (UGCF-Rice), a standardized system for data collection, cross-program benchmarking, identifying key cost drivers, efficiency gaps, and opportunities for optimization. The framework’s effectiveness was demonstrated through case studies costing four National Agricultural Research and Extension System (NARES) rice breeding pipelines in South Asia (India and Nepal) and Sub-Saharan Africa (Tanzania and Ghana), using UGCF-Rice in conjunction with the University of Queensland’s Breeding Program Costing Tool (UQ-BPCT). This comprehensive analysis revealed that rice breeding pipeline costs ranged from USD 26,781 to 39,221, excluding institutional overheads and cross-cutting charges. Costing of two restructured pipelines integrating speed breeding technologies, demonstrated that strategic modernization can greatly enhance efficiency, achieving a 2.3-fold reduction in breeding cycle time, a 17–24-fold increase in throughput (fixed lines per cross), and a 1.6–20-fold reduction in land use compared to conventional breeding. This global costing framework establishes a data-driven foundation for strategic research investment and optimization, empowering policymakers, donors, and breeders to enhance efficiency, sustainability, and impact in rice breeding. Building on these insights, we propose an integrated “Cost-efficient Rice Breeding and Innovation Model” to empower NARES for global impact.